Manajemen Risiko sebagai Upaya Menjaga Stabilitas dan Reputasi Brand Vixzy89 di Pasar Digital - Indy Fauziah Hanifa; Lailafitri Pratiwi; Amelia Rahmadani; Nabila Syaharani; Alfiana (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
The growth of digital business requires companies to be able to manage risks systematically to maintain stability and brand reputation. The development of the digital market also brings both opportunities and challenges for fashion UMKM, including the Vixzy89 brand. The competitive digital business environment requires companies to have the ability to identify, analyze, and control risks that could potentially disrupt operational stability and brand reputation based on ISO 31000 principles. This study aims to analyze the implementation of risk management in the Vixzy brand, an UMKM engaged in the production and sale of women's sandals and flat shoes. The research method uses a qualitative approach through direct interviews with the business owner and observation of business processes. The results of the study indicate that the main risks faced by Vixzy come from the production process, suppliers, demand fluctuations, digital competition, negative reviews, and distribution risks. Through risk management such as quality control, supplier diversification, price adjustments, and customer service strategies, Vixzy is able to maintain operational stability and brand image in the digital market. SWOT analysis and risk matrix show that the company is in a growing position and has great opportunities to expand its market through digitalization and product quality enhancement.